THE MULTICODE CHARACTER OF A WORK OF ART - Abduraximova, Noila Abduxalil kizi (Innovative Development in Educational Activities, 2022)
The article concerns the phenomenon of multicode character of a text regarded as its semiotic heterogeneity. The author analyses interrelation between code heterogeneity, intertext and supertext.